2021
DOI: 10.1038/s41598-021-89426-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various weight loss interventions on serum NT-proBNP concentration in severe obese subjects without clinical manifest heart failure

Abstract: Obesity is associated with a “natriuretic handicap” indicated by reduced N-terminal fragment of proBNP (NT-proBNP) concentration. While gastric bypass surgery improves the natriuretic handicap, it is presently unclear if sleeve gastrectomy exhibits similar effects. We examined NT-proBNP serum concentration in n = 72 obese participants without heart failure before and 6 months after sleeve gastrectomy (n = 28), gastric bypass surgery (n = 19), and 3-month 800 kcal/day very-low calorie diet (n = 25). A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Our results confirm the importance of determining NT-proBNP in patients with comorbid pathology, namely, AH in combination with Т2DM and obesity is a prognostically significant parameter of heart failure in this patient group. Our study is consistent with other authors who have studied the importance of NT-proBNP in the development of cardiovascular complications in patients with monopathology of AH, T2DM, and obesity [12][13][14][15][16][17][18].…”
Section: Ah Ah + Obesity Ah + т2dm Ah + Obesity + т2dmsupporting
confidence: 93%
“…Our results confirm the importance of determining NT-proBNP in patients with comorbid pathology, namely, AH in combination with Т2DM and obesity is a prognostically significant parameter of heart failure in this patient group. Our study is consistent with other authors who have studied the importance of NT-proBNP in the development of cardiovascular complications in patients with monopathology of AH, T2DM, and obesity [12][13][14][15][16][17][18].…”
Section: Ah Ah + Obesity Ah + т2dm Ah + Obesity + т2dmsupporting
confidence: 93%
“…However, data regarding the effect of weight loss on natriuretic peptides are conflicting. While prior observational studies have demonstrated an increase in NP concentrations following weight loss, [26][27][28] with markedly improved NP response to saline loading, 26 the recent STEP-HFpEF trial demonstrated a reduction in both weight and NPs with use of the GLP1-RA semaglutide, with resultant improvement in HF-related symptoms, functional capacity and a reduction in HF events. 29 As such, the putative mechanisms underlying the relationship between the NP system and obesity warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Results. Obese patients had a smaller sum of B-lines according to lung ultrasound than overweight patients and those with normal weight [33 (21-51); 38 (27-54), and 42 (30-58), respectively; p = 0.002] and a lower level of 404 (1,630;5,516); 4,458 (2,697; 5,969); 5,085 (2,871; 7,351) pg / ml, respectively, p = 0.013]. The IVC diameter did not differ significantly depending on body mass index (BMI): with obesity -2.3 (1.9-2.8) cm, with overweightness -2.3 (1.9-2.8) cm, and with normal weight -2.2 (1.8-2.4) mm, p = 0.324.…”
Section: Methodsmentioning
confidence: 99%
“…Upon admission, all patients underwent a standard clinical and laboratory examination, including lung ultrasound with the calculation of the sum of B-lines, IVC ultrasound, and determination of the NT-proBNP level.Results. Obese patients had a smaller sum of B-lines according to lung ultrasound than overweight patients and those with normal weight [33 (21-51); 38 (27-54), and 42 (30-58), respectively; p = 0.002] and a lower level of 404 (1,630;5,516); 4,458 (2,697; 5,969); 5,085 (2,871; 7,351) pg / ml, respectively, p = 0.013]. The IVC diameter did not differ significantly depending on body mass index (BMI): with obesity -2.3 (1.9-2.8) cm, with overweightness -2.3 (1.9-2.8) cm, and with normal weight -2.2 (1.8-2.4) mm, p = 0.324.According to the multivariate Cox regression analysis, the sum of B-lines > 7 at discharge (hazard ratio (HR) 8.90, 95% confidence interval (CI) 2.03-38.30, p = 0.003) and IVC > 2.4 cm at admission (HR 5.42, 95% CI 1.04-28.13, p = 0.045) were independently associated with a higher risk of 12-month mortality from cardiovascular disease.…”
mentioning
confidence: 99%